Analisis Pengaruh Organizational Citizenship Behavior (OCB) dan Komitmen Organisasional terhadap Turnover Intention Perawat di Rumah Sakit Mekar Sari - Susanti, Vivi; Wahidi, Kemala Rita (Lembaga Penerbitan Universitas Esa Unggul, 2020)
The high turnover of nurses in hospitals requires more attention because turnover can harm the organization, both in terms of costs, resources, and the effectiveness of nursing itself. The objectives to be achieved in this study were to analyze the influence of Organizational Citizenship Behavior (OCB) and Organizational Commitment on Nurse Turnover Intention at Mekar Sari Hospital. This study, the author uses a quantitative approach, survey method with questionnaires and the analytical method used is the Multiple Linear Regression test. The population in this study were all nurses at Mekar Sari Hospital, namely 113 nurses. The results of this study are variables of organizational citizenship behavior (OCB) and organizational commitment that have a simultaneous effect on nurse turnover intention at Mekar Sari Hospital. Variable organizational citizenship behavior (OCB) has a negative and significant effect on nurses' turnover intention at Mekar Sari Hospital. Organizational commitment variables have a negative and significant effect on nurses' turnover intention at Mekar Sari Hospital. Implications for Mekar Sari Hospital Management, the results showed that one of the factors that caused low nurse Organizational Citizenship Behavior (OCB) was the workload of nurses, therefore it was hoped that management would pay attention to the workload of nurses by calculating the overall workload of nurses in the Hospital Mekar Sari and provide facilities that support nurses in improving Organizational Citizenship Behavior (OCB). The results showed that one of the factors that led to the nurses' Organizational Commitment was nurse job satisfaction such as salary and career path. Therefore it is important for management to develop nurse Organizational Commitments and pay attention to the needs of nurses by providing satisfaction in work.Keywords: Organizational Citizenship Behavior (OCB), Organizational Commitment, and Nurse Turnover Intention